The Digital Literacy Academic Writing Scale: Exploratory Factor Analysis - Salim Nabhan; Anita Habók (SAGE Open)
As the integration of digital technologies continues to shape academic landscapes, assessing digital literacy in the context of academic writing becomes paramount. Several instruments and frameworks are available for measuring digital literacy and examining it from different perspectives; however, none are suitable for measuring the digital literacy of pre-service teachers in academic domains with psychometric validity. To address this need, the study aims to investigate the validity and reliability of the Digital Literacy Academic Writing Scale. The study recruited 368 pre-service teachers from a teacher training department at a university in Indonesia. Exploratory factor analysis (EFA) was used to explore the factor structure of the scale, which resulted in seven factors, namely, critical thinking, online safety skills, digital culture, collaboration and creativity, finding information, communication, and functional skills, comprising a total of 46 items. The findings demonstrated that Kaiser–Meyer–Olkin measure of sampling adequacy index was .837, and Bartlett’s test p -value = .000 < .05. This result indicates that the analysis is feasible for this data set. Additionally, the overall Cronbach’s alpha value to determine the internal consistency was .949, signifying strong reliability. The findings imply that the instrument is valid and reliable for assessing teachers’ digital literacy in academic writing.